IGFBP-5 overexpression as a poor prognostic factor in patients with urothelial carcinomas of upper urinary tracts and urinary bladder. Issue 7 (28th March 2013) - Liang, Peir-In; Wang, Yu-Hui; Wu, Ting-Feng; Wu, Wen-Ren; Liao, Alex C; Shen, Kun-Hung; Hsing, Chung-Hsi; Shiue, Yow-Ling; Huang, Hsuan-Ying; Hsu, Han-Ping; Chen, Li-Tzon; Lin, Ching-Yih; et al.
Abstract : Background: Urothelial carcinoma (UC) is prevalent worldwide. Dysregulation of cell growth is a critical event of tumorigenesis and has not been assessed systemically in UC. We thus assessed the published transcriptome of urinary bladder urothelial carcinoma (UBUC) and identified insulin-like growth factor-binding protein-5 (IGFBP-5) as the most significantly upregulated gene associated with the regulation of cell growth. Moreover, validated by using public domain data set, IGFBP-5 expression also significantly predicted worse outcome. IGFBP-5 is one of the binding proteins that regulate insulin-like growth factors (IGFs) and its significance has not been comprehensively evaluated in UCs. Methods: Using immunohistochemistry, we evaluated the IGFBP-5 expression status and its associations with clinicopathological features and survival in 340 cases of upper urinary tract urothelial carcinoma (UTUC) and 295 cases of UBUC. Western blot analysis was used to evaluate IGFBP-5 protein expression in human urothelial cell (HUC) lines. Results: IGFBP-5 overexpression was significantly associated with advanced pT stage (p<0.001), high histological grade (UTUC, p<0.001; UBUC, p=0.035), lymph node metastasis (UTUC, p=0.006; UBUC, p=0.004), vascular invasion (UTUC, p<0.001; UBUC, p=0.003), perineural invasion (UTUC, p=0.034; UBUC, p=0.021) and frequent mitosis (UTUC, p<0.001; UBUC, p=0.023). IGFBP-5 overexpression also independently predicted poor disease-specific survival and metastasis-free survival in both groups of patients. Western blot analysis showed IGFBP-5 protein as overexpressed in human urothelial cancer cell lines and not in normal urothelial cancer cells. Conclusions: IGFBP-5 plays an important role in tumour progression in UC. Its overexpression is associated with advanced tumour stage and conferred poorer clinical outcome.